2022
DOI: 10.1111/acer.14961
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic‐related changes in utilization of telehealth and treatment overall for alcohol use problems

Abstract: Background: During the COVID-19 pandemic, specialty alcohol treatment transitioned rapidly to telehealth, which may have created barriers for some patients but increased access for others. This study evaluated the impact of the COVID-19 pandemic on alcohol treatment utilization and potential disparities. Methods: We analyzed electronic health record and claims data from Kaiser Permanente Northern California for adults with alcohol use problems (alcohol use disorder or unhealthy alcohol use diagnoses) during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These differences seem to be explained by less telehealth use by older patients, consistent with prior studies that suggest a digital divide by age, [49][50][51] but could also signify that the transition to telehealth may have helped to attract younger patients, who have shown low treatment initiation rates in prepandemic studies. 23,24 Similar age differences have been reported in studies examining telehealth treatment for other conditions in this health care system 27 and other settings. 52 The health care system's strategies to support telehealth use (eg, previsit calls and tech-checks) may have helped to prevent an increasing digital divide for older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences seem to be explained by less telehealth use by older patients, consistent with prior studies that suggest a digital divide by age, [49][50][51] but could also signify that the transition to telehealth may have helped to attract younger patients, who have shown low treatment initiation rates in prepandemic studies. 23,24 Similar age differences have been reported in studies examining telehealth treatment for other conditions in this health care system 27 and other settings. 52 The health care system's strategies to support telehealth use (eg, previsit calls and tech-checks) may have helped to prevent an increasing digital divide for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Limited evidence suggests that racial and ethnic disparities in addiction treatment utilization have persisted or worsened during the pandemic, 15,17,18 while other studies of alcohol and behavioral health problems have not found increased disparities. 20,26,27 While patients with limited technology access or skills (eg, patients with low income and older adults [28][29][30][31] ) may have faced increased barriers to care during the pandemic, others may have found telehealth services to be more flexible and convenient, eliminating barriers such as transportation time and cost, the need for childcare, and stigma or anxiety related to attending in-person treatment. 32,33 Greater understanding of changes in addiction treatment utilization during the COVID-19 pandemic among various subgroups of patients with drug use problems can help to tailor care as telehealth becomes more established in addiction treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the number of individuals living with managed opioid use disorder is increasing, at least partially due to improved treatment strategies including more widely available methods of medication for opioid use disorder and overdose reversal. 59 60 Care coordination between a patient's current prescriber and surgeon is essential to ensure appropriate postoperative pain control and prescription management. Lack of coordination can increase the probability of high-risk prescribing practices, lack of rescue medications when needed, poor pain control, and an increased risk of opioid-related harms after their surgery.…”
Section: Caring For Individuals At Risk For Poor Pain and Opioid-rela...mentioning
confidence: 99%
“…Other studies outside of the VHA have found that the transition to telehealth may have attracted subgroups of individuals who have historically underutilized care for alcohol use problems, particularly younger and healthier adults, without exacerbating prepandemic racial and ethnic disparities in treatment utilization. (Palzes et al, 2022). Additional reasons for observed differences across treatment modalities may be related to the greater use of telehealth in some groups to mitigate barriers to AUD treatment, including distance, transportation, and stigma.…”
Section: Any Telehealth Visit Only In-person Visits P-value C Any Vid...mentioning
confidence: 99%